2018
DOI: 10.1038/s41598-018-21823-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of CEMIP and CA 19-9 enhances diagnostic accuracy for pancreatic cancer

Abstract: Carbohydrate antigen (CA) 19-9 is the only diagnostic marker used in pancreatic cancer despite its limitations. Here, we aimed to identify the diagnostic role of CEMIP (also called KIAA1199) combined with CA 19-9 in patients with pancreatic cancer. A retrospective analysis of prospectively collected patient samples was performed to determine the benefit of diagnostic markers in the diagnosis of pancreatic cancer. We investigated CEMIP and CA 19-9 levels in 324 patients with pancreatic cancer and 49 normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…The diagnostic value of CA19-9 may, in the future, be improved by measuring the antigen on individual proteins or using it in combination with additional markers. In the distinction of PDAC from benign disease and healthy controls, Lee et al 78 reported an improved AUC using a combination of CA19-9 and CEMIP (cell migration-inducing hyaluronan binding protein), a protein involved in the degradation of hyaluronan. compared to CA19-9 alone (0.94 vs 0.89).…”
Section: Current Promising Biomarkers For the Early Detection Of Pdacmentioning
confidence: 99%
“…The diagnostic value of CA19-9 may, in the future, be improved by measuring the antigen on individual proteins or using it in combination with additional markers. In the distinction of PDAC from benign disease and healthy controls, Lee et al 78 reported an improved AUC using a combination of CA19-9 and CEMIP (cell migration-inducing hyaluronan binding protein), a protein involved in the degradation of hyaluronan. compared to CA19-9 alone (0.94 vs 0.89).…”
Section: Current Promising Biomarkers For the Early Detection Of Pdacmentioning
confidence: 99%
“…Results suggest that CEMIP proteins were highly expressed in patients with PDAC compared to healthy individuals. Combining the use of CA 19-9 and CEMIP significantly increased the sensitivity and specificity in discriminating not only patients with all stage pancreatic cancer, but also patients with stage I/II pancreatic cancer from healthy individuals [ 26 ].…”
Section: Ca 19-9mentioning
confidence: 99%
“…In the last decade, different biomarkers have been explored to identify a simpler tool for pancreatic cancer diagnosis and prognosis [8,9] . The development of tumour biomarkers are essential to precisely detect patients at their early stage of tumour growth, as well as to evaluate the treatment responses so that the current therapeutic strategies can be further improved [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, different biomarkers have been explored to identify a simpler tool for pancreatic cancer diagnosis and prognosis [8,9] . The development of tumour biomarkers are essential to precisely detect patients at their early stage of tumour growth, as well as to evaluate the treatment responses so that the current therapeutic strategies can be further improved [8][9][10][11] . Among various validated tools, alcohol dehydrogenase (ADH) isoenzymes, aldehyde dehydrogenase (ALDH) enzyme as well as carbohydrate antigen have been explored as the most common tumour markers for pancreatic cancer [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation